The biophysical bases of will-less behaviors - Perez Velazquez, Jose Luis (Frontiers in Integrative Neuroscience, 2012)
Are there distinctions at the neurophysiological level that correlate with voluntary and involuntary actions? Whereas the wide variety of involuntary behaviours (and here mostly the deviant or pathological ones will be considered) will necessarily be represented at some biophysical level in nervous system activity, for after all those cellular activity patterns manifest themselves as behaviours and thus there will be a multiplicity of them, there could be some general tendencies to be discerned amongst that assortment. Collecting observations derived from neurophysiological activity associated with several pathological conditions characterised by presenting will-less actions such as Parkinson’s disease, seizures, alien hand syndrome and tics, it is proposed that a general neurophysiologic tendency of brain activity that correlates with involuntary actions is higher than normal synchrony in specific brain cell networks, depending upon the behaviour in question. Wilful, considered normal behaviour, depends on precise coordination of the collective activity in cell ensembles that may be lost, or diminished, when there are tendencies towards more than normal or aberrant synchronization of cellular activity. Hence, rapid fluctuations in synchrony is associated with normal actions and cognition while less variability in brain recordings particularly with regards to synchronization could be a signature of unconscious and deviant behaviours in general.